1Pyridine and phosphine functionalised N-heterocyclic carbene complexes of rhodium and iridium - Stylianides, Neoklis; Danopoulos, Andreas A.; Tsoureas, Nikolaos (Journal of Organometallic Chemistry, 2005)
The pyridine functionalised N-heterocyclic carbene complexes [M(κ2-NCDIPP)(COD)]+A-, NCDIPP=3-(2,6-Pr2iC6H3)-1-[2-(3-picolyl)]-imidazol-2-ylidene, A-=[Ar4FB]-, [{3,5-(CF3)2C6H2}4B] -, M = Rh, 1b, Ir, 4, have been prepared in two steps by reaction of the [M(COD)Cl]2 with the isolated NCDIPP to [Rh(κ1-NCDIPP)(COD)Cl], 2, and [Ir(κ 2-NCDIPP)(COD)Cl], 3, followed by anion exchange with Na+A-. The phosphine functionalised N-heterocyclic carbene complex [Rh(PCH2Cmes)2]Br, 6, PCH 2Cmes = 1-(diphenylphosphino-methyl)-3-(2,4,6-Me 3C6H2)-imidazol-2-ylidene, was prepared by the reaction of the [Rh(COD)Cl]2 with the corresponding N-heterocyclic carbene generated in situ. Monomeric [Rh(PCH2CH2C DIPP)(acac)], 7 was prepared by an analogous reactions from [Rh(COE)2(acac)]. In contrast, phosphine functionalised N-heterocyclic carbene complexes of iridium (I) were not easily accessible. However, the reaction of [Ir(COD)(μ-Cl)2(μ-H)]2 with PCH 2CH2Cmes gave complex [Ir(COD)(PCH 2CH2Cmes)Br], 8, in which the carbene is coordinated to the metal in an 'abnormal' mode. © 2005 Elsevier B.V. All rights reserved.
Keywords: Arduengo carbene; crystal structure; Functionalised heterocyclic carbene; Iridium; Pyridine; Rhodium